(untitled) (Journal of Information and Communication Technology, 2023)
Game-based psychotherapy intervention is a promising alternative to non-pharmacological approaches in treating memory disorders. Nevertheless, the game-based approach is yet to be included systematically in existing intervention models for treating memory disorders. Hence, this article discusses how a proposed gamebased psychotherapy intervention is developed and validated using neurofeedback approach. The proposed model consists of nine exogenous and six instantaneous factors as the main components. To ensure its applicability, a validation procedure has been carried out through a series of psychotherapy experiments involving the elderly with memory disorder symptoms. Electroencephalogram (EEG) data captured from the experiments are thoroughly analysed to validate relationships among factors in the model. Experimental findings have proven that all relationships are successfully validated and supported except for the belief component with the cut-off point of 56.6%. The novelty of this study can be attributed to the integration of digital games and neurofeedback in psychotherapy for memory disorders. The model is believed to be a guideline in planning suitable cognitive training and rehabilitation for people with memory disorders towards improving the quality of the elderly life.